Faktor yang Mempengaruhi Pengetahuan Ayah Ketika Anak Mengalami Diare di Provinsi Aceh - Amelya Febryana; Nopa Arlianti; Anwar Arbi (SEHATI: Jurnal Kesehatan, 2025)
Knowledge about the amount of fluid given when a child has diarrhea is one of the problems that occurs in Aceh, where every year there can be an increase and decrease in the level of knowledge among the community, especially among fathers. The study aims to determine the factors that influence fathers' knowledge about the amount of fluid given when a child has diarrhea in Aceh Province in 2017. This study is an analytical survey conducted using secondary data from the 2017 SDKI with a cross-sectional design. The population is all fathers in Aceh Province in 2017 according to the age of 20-54 years as many as 400 respondents. Data analysis using multiple logistic regression tests. The results of the study showed that there was an influence of fathers' knowledge about the amount of fluid given when a child had diarrhea, namely 30-39 years old (OR = 0.14, p = 0.001) and 20-29 years old (OR = 0.14, p = 0.002). Meanwhile, those that had no influence on father's knowledge about the amount of fluid given when a child had diarrhea were upper middle wealth quintile (p=0.596, OR=0.78), middle wealth quintile (OR=0.81, p=0.631), lower middle wealth quintile (OR=0.93, p=0.842), lowest wealth quintile (OR=0.64, p=0.326), age 40-49 years (OR=0.36, p=0.077), area of residence (OR=1.05, p=0.846), secondary education (OR=1.23, p=0.554), primary education (OR=1.92, p=0.155), no schooling (OR=1.19, p=0.890), and number of children (OR=1.06, p=0.919). It is hoped that health workers, especially public health workers in the field of health promotion in Aceh Province, will provide counseling on the prevention and treatment of diarrhea, in order to increase fathers' knowledge about the amount of fluids given when a child has diarrhea.